2012
DOI: 10.1136/bjophthalmol-2011-300910
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for anxiety and depression in patients with glaucoma

Abstract: A younger age was thus found to be a risk factor for anxiety, while an older age and increasing glaucoma severity were risk factors for depression in patients with glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 23 publications
8
76
1
1
Order By: Relevance
“…This is in agreement with a study by Mabuchi et al,7 which concluded that increasing glaucoma severity (such as a lower MD in the worse eye) is a risk factor for depression in glaucoma. Sociodemographic variables such as occupation, marital status, and education were not significantly associated with depression or anxiety in our study.…”
Section: Risk Factors For Depression and Anxiety Disordersupporting
confidence: 90%
See 2 more Smart Citations
“…This is in agreement with a study by Mabuchi et al,7 which concluded that increasing glaucoma severity (such as a lower MD in the worse eye) is a risk factor for depression in glaucoma. Sociodemographic variables such as occupation, marital status, and education were not significantly associated with depression or anxiety in our study.…”
Section: Risk Factors For Depression and Anxiety Disordersupporting
confidence: 90%
“…We also excluded patients who had coexisting physical and psychiatric disorders (ie, depression/anxiety), as well as patients who were on any form of medication that was known to possibly lead to psychiatric disorders or cognitive impairment (such as digoxin and steroids), except those on topical b-blockers and carbonic anhydrase inhibitors. The latter exception was made because of controversial evidence as to whether the use of topical bblockers and carbonic anhydrase inhibitors result in depression, 7,12,13 and our interest therefore in investigating the association.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…13e22 In this study, there were significant associations between glaucoma and VA and VF losses and reduced PF, namely, increased anxiety, reduced self-image, and less confidence in health care. Several earlier studies found no correlation between VA or VF loss with patient perceptions of treatment, 19 anxiety, 16 or fear of blindness. 18 However, Parrish et al 21 were at least modestly correlated with vision-specific dependency, role difficulties, social and emotional well-being, and mental health on the National Eye Institute VisionFunction Questionnaire.…”
Section: Discussionmentioning
confidence: 97%
“…In the case of comorbid depression (depression with chronic physical disease) the prevalence was significantly higher, between 9.3% and 23.0%. Depressive disorders were the second leading cause of YLD according to Global Burden of Disease Study 2010 (Ferrari et al 2013) as it was in the Japanese Clinical study (Mabuchi et al 2012). The range of the prevalence of depression in glaucoma patients was between 11.4% and 32.1% in the Australian clinical study performed by Skalicky et and Goldberg (Skalicky & Goldberg 2008).…”
Section: Epidemiological Datamentioning
confidence: 99%